Innovative Technologies For Manufacturing Foam Models And Cast Steel Parts Of Harrow Tooth With Wear-Resistant Carbide Coating By Casting On Gasifyable Models And Their Optimal Thermal Treatment - Tilabov Baxodir Qurbanovich (The American Journal of Engineering and Technology, 2021)
This article describes innovative step-by-step technologies for the manufacture of foam models and cast steel parts of the harrow teeth with a wear-resistant hard-alloy coating by casting on gasified models. Methods of gluing gasified models, the processes of forming, rammers, pouring liquid metal and the formation of cast parts of the harrow teeth are shown. Compositions, microstructures and properties of hard-alloy coatings made of 35GL steel are given. The surface thickness of the coating on the finished harrow tine parts is shown. The hardness and microhardness of the surface and subsurface layers of the samples were determined. Optimal modes of heat treatment with double phase recrystallization for these parts have been developed. It has been proved that heat treatment with double phase recrystallization increases the wear-resistance and durability of finished steel parts by 2-3 times.